New Social Media dan Imagologi Politik Analisis Framing terhadp Konten Politik pada Kanal Youtube Dedi Mulyadi Periode 2021 - Ayu Sabrina Barokah; Hendra Gunawan; Faisal Fadilla Noorikhsan (Epistemik Press, 2023)
Through various choices that are packaged in audio and visual form, it can show the quantity of performance quality that refers to a plus or positive image in accordance with the interests to be achieved. To achieve these interests, various media are used. One of these media is social media. Dedi Mulyadi is a member of the DPR-RI who uses his Youtube account to invite the public to see his appearance directly through a connected network. This research focuses on analyzing content framing on the Kang Dedi Mulyadi Youtube channel. The researcher tries to see how Dedi Mulyadi builds an image in his frame as a competent and transparent member of the DPR-RI. The theoretical basis used is New Media, Imagology, and Framing Analysis. This research is a descriptive qualitative research using Data Analysis Techniques Framing Analysis Model Robert N. Entman. Data collection techniques using text studies, documentation, interviews, and observations. Six videos with three different themes (child-family issues; environment; and professionalism), were selected as primary data obtained from the Kang Dedi Mulyadi Youtube channel. The results of this study indicate that Dedi Mulyadi uses the Youtube channel to publish his work, with the aim that it can be seen and assessed by the public through polls on a connected network.